Estrategias de publicidad aplicando la metodología AIDA para el posicionamiento de la microempresa Xpander - Lema Yépez, Patricia Alexandra (2026)
The research focused on designing advertising strategies using the AIDA method to position the microenterprise Xpander. It identified that, despite offering quality products, the microenterprise lacked well-defined and structured advertising strategies, which limited its visibility. The main objective was to design advertising strategies, for which the AIDA methodology was used, whose stages are: attention, which is based on attracting attention using creative elements that generate impact in the first three seconds; interest, which captures interest with relevant information such as the characteristics and benefits of the product; desire, a phase that generates an emotional link between the product and the needs or aspirations of the consumer; and action, which guides the consumer to take a specific action such as purchasing a product or service. The methodology employed had a mixed approach that combined quantitative and qualitative components, as well as content analysis using Atlas Ti software, complemented by the planning phases of an advertising campaign that required the use of a creative brief as a guide to ensure its effective development. The results revealed consumer behavior patterns, the importance of identifying communication channels according to the preferences of the target audience, and key concepts for designing effective advertising strategies, validated through data triangulation. The research provided theoretical and practical knowledge applicable to similar ventures and demonstrated that the AIDA model is effective as a positioning strategy as long as clear guidelines for its implementation are established.